Состояние и перспективы применения высокоэффективных сварочных технологий - Дилтай, У.; Штайн, Л.; Весте, К.; Райх, Ф. (Автоматическая сварка, 2003)
Рассмотрены некоторые достижения последних лет в области создания высокоэффективных сварочных технологий. Отмечены возможности применения усовершенствованных технологий электронно-лучевой и лазерной сварки. Within the last couple of years, there have been several new developments in the field of high-efficient welding technology. This paper presents these developments, describing their principle, outlining their possibilities and giving examples for their application. Fields addressed are new arc welding processes, latest developments in electron beam welding, as well as trends in laser beam welding concerning processes and equipment.